The philosophy of natural and art religion in the Hegel’s Phenomenology of Spirit - Gómez Navarro, Ángel (2016)
This paper describes the philosophy of natural religion and art, in the deployment of various figures, as it has been developed by Hegel in his Phenomenology of Spirit, taking into account the comments of two philosophers specialists: Jean Hyppolite y Ramón Valls Plana. The purpose is to know how Hegel, not only incorporated to unrevealed religions in his system philosophy and reconstructs its history but also pose the problem of their respective truth.